Identifying neighbourhood and individual resilience profiles for cardiovascular health: a cross-sectional study of blacks living in the Atlanta metropolitan area. Issue 7 (30th July 2021) - Ko, Yi-An; Shen, Jenny; Kim, Jeong Hwan; Topel, Matthew; Mujahid, Mahasin; Taylor, Herman; Quyyumi, Arshed; Sims, Mario; Vaccarino, Viola; Baltrus, Peter; Lewis, Tene
Abstract : Objective: To simultaneously examine multiple individual-level neighbourhood perceptions and psychosocial characteristics and their relationships with cardiovascular health (CVH) among blacks. Design: Cross-sectional study. Setting: Subjects were recruited between 2016 and 2018 via convenience sampling. Participants: 385 Black men and women, age 30–70 living in the Atlanta metropolitan area (Georgia, USA). Primary outcome measure: Individual's CVH was summarised as a composite score using American Heart Association's Life's Simple 7 (LS7) metrics. Methods: We implemented unsupervised learning (k-means) and supervised learning (Bayesian Dirichlet process clustering) to identify clusters based on 11 self-reported neighbourhood perception and psychosocial characteristics. We also performed principal component analysis to summarise neighbourhood perceptions and psychosocial variables and assess their associations with LS7 scores. Results: K-means and Bayesian clustering resulted in 4 and 5 clusters, respectively. Based on the posterior distributions, higher LS7 scores were associated with better neighbourhood perceptions and psychosocial characteristics, including neighbourhood safety, social cohesion, activities with neighbours, environmental mastery, purpose in life, resilient coping and no depression. Taken together, the first principal components of neighbourhood perceptions and psychosocial characteristics were associated with an increase of 0.07 (95% CI −0.17 to 0.31) and 0.31 (95% CI 0.06 to 0.55) in LS7 score, respectively, after accounting for age, sex, household income and education level. Conclusion: Both neighbourhood perception and psychosocial domains were related to CVH, but individual psychosocial characteristics appeared to contribute to CVH most. Approaches that acknowledge the importance of factors in both domains may prove most beneficial for enhancing resilience and promoting CVH among black communities.